Rock physics and geomechanics in the study of reservoirs and repositories - David, C.; Le Ravalec, Mickaële (Geological Society, 2007)
The study of reservoir and repository performance requires the integration of many different fields in Earth sciences, among them rock physics and geomechanics. The aim of this book is to emphasize how rock physics and geomechanics help to get a better insight into important issues linked to reservoir management for exploitation of natural resources, and to repository safety assessment for hazardous waste storage in geological environment.
"Most of the contributions were originally presented at the Euro-conference on Rock Physics and Geomechanics, which was held on 18-22 September 2005 in Ile d'Oléron, France ..."--Preface.
Keywords: Petroleum -- Geology -- Congresses.; Geology, Stratigraphic -- Congresses.; Rock mechanics -- Congresses.; Reservoirs -- Congresses.; Petrology -- Congresses.; Hydrogeology -- Congresses.; elektronické knihy; electronic books